Chasing the Zebra: a case of membranous-like Glomerulopathy with SSA/RO52 deposits and no overt connective tissue disease - Savino Sciascia; Paolo Miraglia; Massimo Radin; Manuela Giarin; Nicolas Charbonier; Antonella Barreca; Irene Cecchi; Irene Lanzetta; Roberta Fenoglio; Elisa Menegatti; Dario Roccatello (BMC Rheumatology, 2023)
Abstract Background The nature of the deposits in immune-mediated glomerulonephritis with a membranous pattern and masked IgG-Kappa deposits (MGMID) remains still to be elucidated. Case presentation We present a case of 33-year-old woman developing a continuous asymptomatic proteinuria (0.8–1 g/24 h) with no overt connective tissue diseases. She tested positive at high titers for SSA antibodies (Ro52 838 UI/mL, Ro60 2716 UI/mL) and at the kidney biopsy histological findings were compatible with an immune-mediated glomerulonephritis with a membranous pattern and masked IgG-Kappa deposits. Also, we demonstrated a positive immunohistochemistry staining for anti-Ro52-SSA antibodies, with a granular positivity in mesangium and along rare glomerular capillaries. To date, only one case of a patient with overt diagnosis of Sjögren’s syndrome with MGMID has been described but a pathogenic role for SSA and SSB antibodies has never been proven. Conclusions In this case, we described for the first time by immunohistochemistry a Ro52+ granular positivity in the mesangium and glomerular capillaries, potentially paving the way for a better understanding of MGMID.